Fonti e strumenti digitali per la conoscenza e la tutela del patrimonio costruito di Roma - Nicoletta Marconi; Ilaria Giannetti; Valentina Florio (Restauro Archeologico, 2023)
The protection, management, and valorization processes of the Built World Heritage, of which the historic center of Rome is an integral part, include the study and use of the historical documents preserved in the archives of the territory. The Corp of Civil Engineering of Rome (Genio Civile di Roma) Found, kept in the State Archives in Rome, is a crucial source for the knowledge of the built heritage of Rome. The Fund holds significant data about the urban development of the city and the intervention to preserve the historic built heritage, from the last three decades of the 19th century – when Rome began as the capital of the unified state of Italy – to the mid of the 20th century. For the valorization of the Found a research agreement between the State Archives of Rome and the University of Rome “Tor Vergata” is established: in this framework, the cataloging and the study of this unique documentary heritage are correlated with integrated digital tools.